1982
DOI: 10.1139/m82-019
|View full text |Cite
|
Sign up to set email alerts
|

Halocins: salt-dependent bacteriocins produced by extremely halophilic rods

Abstract: Strains of halophilic rods, presumably halobacteria, produce substances that inhibit the growth of other halobacteria but not halococci or moderate halophiles. The spectrum of action of these substances, called "halocins," was determined on 39 halobacteria or presumed halobacteria. The properties of halocin H4, produced by strain R-4, were studied using Halobacterium halobium as an indicator organism. Halocin H4 is adsorbed by the indicator organism and causes both death and lysis. It is a high molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 7 publications
0
82
0
Order By: Relevance
“…As such, halocins are the haloarchaeal equivalent of the well-characterized protein antibiotics called bacteriocins that are produced by some 30 genera of the domain Bacteria (2). The term "halocin" was coined in 1982 by Francisco Rodriguez-Valera, who assumed that these substances were bacteriocins and who logically applied a similar nomenclature (28). Although archaeons share a "prokaryotic" cellular organization and morphological motif with members of the domain Bacteria, they are in separate domains and are only distantly related (41).…”
mentioning
confidence: 99%
“…As such, halocins are the haloarchaeal equivalent of the well-characterized protein antibiotics called bacteriocins that are produced by some 30 genera of the domain Bacteria (2). The term "halocin" was coined in 1982 by Francisco Rodriguez-Valera, who assumed that these substances were bacteriocins and who logically applied a similar nomenclature (28). Although archaeons share a "prokaryotic" cellular organization and morphological motif with members of the domain Bacteria, they are in separate domains and are only distantly related (41).…”
mentioning
confidence: 99%
“…Halocins are haloarchaeal equivalents of eubacterial bacteriocins (2) and were first discovered in 1982 by F. RodriguezValera (24). Although nearly universal in halobacterial rods (17,32), only three halocins have been characterized in any detail: halocin H4 from Haloferax mediterranei R4 (15,16), halocin H6 from Haloferax gibbonsii Ma2.39 (30,31), and halocin HalR1 from Halobacterium sp.…”
mentioning
confidence: 99%
“…Further examination of the cytocidal TuA4 supernatant revealed that the lethal component was a secreted protein, since haloarchaeal cell lysates were not toxic and the toxic activity could be abolished by thermophilic protease treatment. Peptide antibiotics have been identified as excreted products for numerous haloarchaea (29) and have been termed halocins (22) or microhalocins (20). The mechanism of action and target are known only for halocin H6, a Na ϩ /H ϩ antiporter inhibitor (16).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sulfolobus islandicus produces an insoluble cell-associated peptide, termed a sulfolobicin, which is specific only for closely related species (19). Halophilic archaea secrete peptide antibiotics called halocins (or, if small, microhalocins) upon entry into stationary phase and in some cases after entry into stationary phase (20,22,26,28,29).…”
mentioning
confidence: 99%